EFFECTS OF PROPRIETARY VITAMIN-MINERAL PREMIXES AND HOUSING SYSTEMS ON LAYING CHICKENS EGG PRODUCTION AND QUALITY INDICES (2016)
Housing Systems (HS), dietary vitamins and mineral supplements are obligatory components of poultry production. The composition of Proprietary Vitamin-mineral Premixes (PVmP) varies in forms and source which alongside HS could alter production and quality of eggs. There is dearth of information on effects of HS and different PVmP on production and quality indices of eggs. Therefore, effects of five PVmP and two HS on egg production and quality indices were investigated in Ibadan. A basal diet was formulated without any PVmP (control diet, D1), while others were supplemented with 0.25% premixes K, L, M, N and P each to obtain diets D2, D3, D4, D5 and D6, respectively. In a completely randomised design, Bovan Nera pullets (n=576) aged 13 weeks were randomly allocated to two HS [Battery Cage (BC) and Deep Litter (DL)] and six treatments in a 2x6 factorial arrangement, and reared for ten months. Ambient temperature and Relative Humidity (RH) in HS were recorded. Hen Day Egg Production (HDEP) was assessed at peak and late-lay phases by standard procedure. Eggs collected at week 36 were stored for 28 days and assayed for Crude Protein (CP), Low Density Lipoprotein-cholesterol (LDLc), Lipid Oxidation (LO), Eggshell Weight (EW), Eggshell Thickness (ET) and Haugh Unit (HU) at 0, 7, 14, 21, 28 Days of Storage (DoS) under ambient conditions. Data were analysed using descriptive statistics, polynomial regression and ANOVA at α0.05. Ambient temperature (oC) and RH (%) ranged from 26.5±0.1 to 31.9±1.1and 40.6±1.0 to 90.5±8.7, respectively and were above thermoneutrality for chickens. Hens attained peak-lay at different periods during production irrespective of HS and PVmP type. The HDEP (%) in BC (64.1±26.4) and DL (82.0±13.8) at peak-lay reduced to 52.1±11.4 and 57.8±14.1, respectively in late-lay. The HDEP on D1 at peak-lay declined from 56.1±9.6 to zero at week 34. At week 34, HDEP in K (76.65) and M (76.60) were higher than 68.45, 68.59 and 67.72 obtained for birds on L, N and P respectively. At week 36, CP (%) of eggs from hens on D2 (11.6±0.17), D3 (11.55±0.23), D5 (11.55±0.23) and D6 (11.6±0.23) were higher than those on D4 (11.4±0.17). The LDLc (mg/dL) and LO (μmol/g) of egg from hens on DL (2.13±1.63 and 0.04±0.01, respectively) were higher than BC (0.74±0.15 and 0.028±0.01μmol/g, respectively). At zero DoS, LO (μmol/g) of egg from hens on D2 (0.028±0.009), D3 (0.031±0.008), D4 (0.033±0.008), D5 (0.032±0.008) and D6 (0.027±0.010) were significantly different and increased linearly with DoS. The EW and ET of eggs from BC (5.89±0.60 and 0.35±0.03) were significantly higher than in DL (5.58±0.48 and 0.34±0.03, respectively). Eggs from BC (48.7±24.6) had higher HU than DL (44.8±25.2). The HU of egg from hens on D5 (48.6±25.2) and D6 (48.0±25.0) were significantly higher than D2 (46.1±26.8), D3 (46.1±23.8) and D4 (44.8±25.1), and HU decreased significantly with DoS (R² = 0.98). Birds raised on deep litter produced more eggs than battery cage system. Proprietary vitamin-mineral premix P reduced egg lipid oxidation, while interaction of proprietary vitamin-mineral premixes L and N with both housing systems enhanced bird laying capability